A review on the kenaf/glass hybrid composites with limitations on mechanical and low velocity impact properties - Ahmad Nadzri, Seri Nur Zumaimi; Hameed Sultan, Mohamed Thariq; Md Shah, Ain Umaira; Safri, Syafiqah Nur Azrie; Basri, Adi Azriff (MDPI, 2020)
Environmental awareness and trends to develop sustainable resources have directed much research attention towards kenaf fibre as an alternative reinforcement in composite manufacturing. Numerous studies have been conducted on kenaf and its hybrid composites. Most studies were conducted on kenaf/glass hybrid composites compared to other kenaf/synthetic hybrid composites. Similar with other materials, mechanical properties were the fundamental knowledge identified by the researcher. Limited studies conducted on other properties have restricted the use of kenaf composites to non-structural applications. To extend the potential of kenaf composites to automotive exterior or other critical applications, studies on impact properties can be a valuable contribution in the material field. This review discusses the mechanical and low velocity impact properties of kenaf/glass hybrid composites reported previously. Percentage loading of fibre, the angle of orientation in woven fibres and the chemical treatment applied to the fibre before compounding are the three major parameters that affect the mechanical and impact properties of the composites. This review provides insights into the mechanical and impact properties of kenaf/glass hybrid composites for future research.